(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2024)
Tillage practices make up one of the most essential operations executed on the soil during crop production. They manipulate the soil by mechanical means using tools, implements, and powered machinery with the intention to prepare the soil and make it suitable for plant growth. For the adoption of sustainable agriculture, tillage practices carried out in a particular region and their consequences on soil health need to be assessed. This review article identified traditional, conventional, and conservation tillage as the major tillage systems employed by farmers during crop cultivation in the North West Region of Cameroon. Traditional tillage practices (traditional ridging, burning in ridges (“Ankara”), and slash and burn) were highly predominant especially among small-holder farmers, followed by conservation tillage. Conventional tillage practices were the least practiced among farmers. Due to the less adoption of conventional and conservation tillage, soils in the region are mainly affected by the identified widely used traditional tillage practices. Traditional ridging exerted beneficial effects on the soil such as improved soil water conservation, increased soil nitrogen, and soil organic matter contents while burning in ridges and slash and burn exerted negative consequences on the soil by declining soil fertility, destroying soil physical properties and reducing overall land productivity. Due to the adoption of poor tillage techniques, soil degradation is rampant in the region placing the population at risk of low land productivity and food insecurity. The adaptation of improved tillage practices such as traditional ridging is thus required for sustainable soils and increased food security. Int. J. Agril. Res. Innov. Tech. 14(1): 70-76, June 2024